Pathogenic variation of Phakopsora pachyrhizi infecting soybean in Nigeria - Twizeyimana, M.; Ojiambo, P.S.; Sonder, Kai; Ikotun, T.; Hartman, G.L.; Bandyopadhyay, Ranajit (Scientific Societies, 2009)
Soybean rust, caused by Phakopsora pachyrhizi, is an important disease in Nigeria and many other soybean-producing countries world-wide. To determine the geographical distribution of soybean rust in Nigeria, soybean fields were surveyed in the Derived Savanna (DS), Northern Guinea Savanna (NGS), and Southern Guinea Savanna (SGS) agroecological zones in Nigeria between 2004 and 2006. Disease severity in each zone was determined and analyzed using geostatistics. Prevalence of infected fields and disease severity in surveyed fields were signifi-cantly (P <0.05) different between geographical zones with both vari-ables being higher in the DS zone than in either NGS or SGS zones. Geostatistical analysis indicated that the spatial influence of disease severity at one location on severity at other locations was between 75 and 120 km. An exponential model best described the relationship between semivariance and lag distance when rust severity was high. Spatial interpolation of rust severity showed that locations in the DS zone were more conducive for the rust epidemic compared to areas in the NGS zone. In the 2005 survey, 116 purified isolates were established in culture on detached soybean leaves. To establish the nature of pathogenic variation in P. pachyrhizi, a set of four soybean accessions with Rpp1, Rpp2, Rpp3, and Rpp4resistance genes, two highly resistant and two highly susceptible genotypes were inoculated with single uredinial isolates. Principal com-ponent analysis on the number of uredinia per square centimeter of leaf tissue for 116 isolates indicated that an adequate summary of pathogenic variation was obtained using only four genotypes. Of these four, PI 459025B (with Rpp4 gene) and TG× 1485-1D had the lowest and highest number of uredinia per square centimeter, respectively. Based on cluster analysis of the number of uredinia per square centimeter, seven pathotype clusters were determined. Isolates in cluster III were the most virulent, while those in cluster IV were the least virulent. Shannon’s index (H) revealed a more diverse pathogen population in the DS zone (H = 1.21) compared to the rust population in SGS and NGS with H valuesof 1.08 and 0.91, respectively. This work will be useful in breeding and man-agement of soybean rust by facilitating identification of resistant geno-types and targeting cultivars with specific resistance to match prevailing P. pachyrhizi pathotypes in a given geographical zone.